EDUKASI PEDOMAN GIZI SEIMBANG (PGS) TERHADAP PENGETAHUAN DAN SIKAP SISWA SMP NEGERI 1 BARRU - Abdullah Tamrin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
ABSTRACT One of the efforts to increase knowledge is by providing education about health, especially about nutrition. Education of nutrition is an activity to convey a health message to the community or group in order to give a direct impact their knowledge and attitude development. This study aims to find out the effect of education of balanced nutrition guidelines towards students’ knowledge and attitude of SMP Negeri 1 Barru. The type of research used was a pre-experimental study with design of one group pre-test and post-test design conducted in SMP Negeri 1 Barru by involving 250 students as samples at the grade VII and VIII which was obtained by using simple random sampling. The sampling process was conducted on May 15 - May 17 2019. The results of the research conducted at SMP Negeri 1 Barru showed that students' knowledge before being given good nutrition knowledge was (60%), while after being given education of nutrition, it increased to good (80.4% ) by using the Wilcoxon statistical test and obtained a value (p = 0,000) which means that there is an effect of education of nutrition towards students’ knowledge. The students’ attitude before being given education of nutrition was (32%) as students at the good level, while after being given education of nutrition, it increased to good (64.8%) by using the Wilcoxon statistical test and obtained a value (p = 0,000) which means there is an effect of education of nutrition towards students’ attitude. The level of students’ nutrition knowledge and attitudes increased after education of nutrition was conducted and there was a significant effect indicated by the value of p = 0,000 (p <0.05).